ELECTRONIC PHASES OF THE IONIC HUBBARD MODEL WITH COULOMB DISORDER - Thi Hai Yen, Nguyen; Anh Tuan, Hoang; Duc Anh, Le (HNUE Journal of Science: Journal of Natural Sciences, 2026)
We investigate the effects of Coulomb disorder on the half-filled ionic Hubbard model within the framework of dynamical mean-field theory (DMFT), using the equation-of-motion method as the impurity solver, combined with typical medium theory (TMT). In contrast to conventional disordered Hubbard models, the ionic Hubbard model contains a staggered ionic potential that introduces additional competition between band-insulating and correlation-driven insulating tendencies. We analyze how this ionic potential modifies the electronic phases induced by Coulomb disorder through the arithmetic and geometric averages of the local density of states. In the absence of disorder, the system exhibits metallic (M), Mott-insulating (MI), and band-insulating (BI) phases. When Coulomb disorder is introduced, Anderson-insulating (AI) behavior and localized states (LS) inside the Mott gap are also observed. In particular, the LS regime appears between the metallic and Mott-insulating phases at small ionic potentials, whereas the AI regime develops for sufficiently large values of the Coulomb interaction and ionic potential. Our results show that the interplay between ionic potential, electron correlation, and disorder substantially influences the localization behavior and insulating characteristics of the ionic Hubbard model.